Persistent fatigue induced by interferon-alpha: a novel, inflammation-based, proxy model of chronic fatigue syndrome. (February 2019) - Russell, Alice; Hepgul, Nilay; Nikkheslat, Naghmeh; Borsini, Alessandra; Zajkowska, Zuzanna; Moll, Natalie; Forton, Daniel; Agarwal, Kosh; Chalder, Trudie; Mondelli, Valeria; Hotopf, Matthew; Cleare, Anthony; et al.
Highlights: Baseline fatigue is not associated with the development of persistent fatigue after IFN-α. IFN-α-induced persistent fatigue is associated with increased baseline IL-10. Patients who develop persistent fatigue experience greater increases in IL-6 and 10 in response to IFN-α. Persistently fatigued patients recover at a similar rate, but from a more severe acute response to the initial trigger. Once established, neither the persistent fatigue phenotype, nor CFS, are associated with peripheral immune activation. Abstract: The role of immune or infective triggers in the pathogenesis of Chronic Fatigue Syndrome (CFS) is not yet fully understood. Barriers to obtaining immune measures at baseline (i.e., before the trigger) in CFS and post-infective fatigue model cohorts have prevented the study of pre-existing immune dysfunction and subsequent immune changes in response to the trigger. This study presents interferon-alpha (IFN-α)-induced persistent fatigue as a model of CFS. IFN-α, which is used in the treatment of chronic Hepatitis C Virus (HCV) infection, induces a persistent fatigue in some individuals, which does not abate post-treatment, that is, once there is no longer immune activation. This model allows for the assessment of patients before and during exposure to the immune trigger, and afterwards when the original trigger is no longer present. Fifty-five patients undergoing IFN-α treatment for chronic HCV were assessed at baseline, during the 6–12 months of IFN-α treatment, and at six-months post-treatment. Measures of fatigue, cytokines and kynurenine pathway metabolites were obtained. Fifty-four CFS patients and 57 healthy volunteers completed the same measures at a one-off assessment, which were compared with post-treatment follow-up measures from the HCV patients. Eighteen patients undergoing IFN-α treatment (33%) were subsequently defined as having 'persistent fatigue' (the proposed model for CFS), if their levels of fatigue were higher six-months post-treatment than at baseline; the other 67% were considered 'resolved fatigue'. Patients who went on to develop persistent fatigue experienced a greater increase in fatigue symptoms over the first four weeks of IFN-α, compared with patients who did not (Δ Treatment Week (TW)-0 vs. TW4; PF: 7.1 ± 1.5 vs. RF: 4.0 ± 0.8, p = 0.046). Moreover, there was a trend towards increased baseline interleukin (IL)-6, and significantly higher baseline IL-10 levels, as well as higher levels of these cytokines in response to IFN-α treatment, alongside concurrent increases in fatigue. Levels increased to more than double those of the other patients by Treatment Week (TW)4 ( p = 0.011 for IL-6 and p = 0.001 for IL-10). There was no evidence of an association between persistent fatigue and peripheral inflammation six-months post-treatment, nor did we observe peripheral inflammation in the CFS cohort. While there were changes in kynurenine metabolites in response to IFN-α, there was no association with persistent fatigue. CFS patients had lower levels of the ratio of kynurenine to tryptophan and 3-hydroxykynurenine than controls. Future studies are needed to elucidate the mechanisms behind the initial exaggerated response of the immune system in those who go on to experience persistent fatigue even if the immune trigger is no longer present, and the change from acute to chronic fatigue in the absence of continued peripheral immune activation.